Everolimus in the treatment of subependymal giant cell astrocytomas, angiomyolipomas, and pulmonary and skin lesions associated with tuberous sclerosis complex - Franz DN (Dove Medical Press, 2013)
David Neal Franz Department of Pediatrics, Tuberous Sclerosis Clinic, Cincinnati Children's Hospital Medical Center, Cincinnati, OH, USA Abstract: Tuberous sclerosis complex (TSC) is an autosomal dominant genetic disorder caused by inactivating mutations in either the TSC1 or TSC2 genes. It is characterized by the development of multiple, benign tumors in several organs throughout the body. Lesions occur in the brain, kidneys, heart, liver, lungs, and skin and result in seizures and epilepsy, mental retardation, autism, and renal and pulmonary organ system dysfunction, as well as other complications. Elucidation of the molecular pathways and etiological factors responsible for causing TSC has led to a paradigm shift in the management and treatment of the disease. TSC1 or TSC2 mutations lead to constitutive upregulation of the mammalian target of rapamycin pathway, which affects many cellular processes involved in tumor growth. By targeting mammalian target of rapamycin with everolimus, an orally active rapamycin derivative, clinically meaningful and statistically significant reductions in tumor burden have been achieved for the main brain (subependymal giant cell astrocytoma) and renal manifestations (angiomyolipoma) associated with TSC. This review provides an overview of TSC, everolimus, and the clinical trials that led to its approval for the treatment of TSC-associated subependymal giant cell astrocytoma and renal angiomyolipoma. Keywords: everolimus, subependymal giant cell astrocytoma, angiomyolipomas, lymphangioleiomyomatosis, facial angiofibromas, tuberous sclerosis complex